2007
DOI: 10.1080/10803548.2007.11076718
|View full text |Cite
|
Sign up to set email alerts
|

The Modal Low Frequency Noise of an Elastically Supported Circular Plate

Abstract: The modal low frequency noise generated by a vibrating elastically supported circular plate embedded into a flat infinite baffle has been examined. The low frequency noise radiation efficiency circular plate hatchwayCorrespondence and requests for offprints should be sent to Wojciech P. Rdzanek,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…(9) and (10) is [21] N. A. Bastián-Monarca and J. P. Arenas Study sound radiation rectangular plate resting elastic foundation (11) where , , , and are mode shapes parameters which can be determined from boundary conditions. The boundary conditions for this case are [22] over (12) over (13) Substituting Eq.…”
Section: Plate Simply Supported On Its Four Edges (Ss-ss-ss-ss)mentioning
confidence: 99%
“…(9) and (10) is [21] N. A. Bastián-Monarca and J. P. Arenas Study sound radiation rectangular plate resting elastic foundation (11) where , , , and are mode shapes parameters which can be determined from boundary conditions. The boundary conditions for this case are [22] over (12) over (13) Substituting Eq.…”
Section: Plate Simply Supported On Its Four Edges (Ss-ss-ss-ss)mentioning
confidence: 99%
“…In Rdzanek et al [4] an exact integral expression for the sound radiation efficiency related to the mode (m, n) is derived from its Hankel representation (see Equation 21 of Rdzanek et al). Evidently, sound radiation efficiency may be dependent on the particular boundary condition at the edge of the circular plate, which can be defined through the appropriate values of p and q.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…In particular, there have been many studies on predicting the sound power radiated from a circular plate [3]. In a recent article, Rdzanek, Rdzanek, Engel, et al reported a motivating study on the modal low-frequency noise generated by a vibrating elastically supported circular plate embedded into a flat infinite baffle [4]. Their approach allows one to estimate the low-frequency sound power radiated from both axisymmetric and asymmetric modes, and virtually for any uniform boundary condition at the contour of the plate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations